Analisis Kandungan Merkuri dan Hidrokuinon pada Krim Pemutih Tanpa Izin Edar yang Beredar Dikota Palu - Rayu Indri Pangesti; Jamaluddin Jamaluddin (Ridwan Institute, 2021)
Whitening cream is a mixture of chemicals and other ingredients such as ingredients that resist sunlight (SPF) and antioxidants such as vitamin E, which can whiten or lighten black spots on the skin. With so many medicinal ingredients on the market that are easily found, many manufacturers add harmful ingredients that are not suitable for use in cosmetic products, one of which is facial whitening creams. The use of dangerous ingredients in facial whitening creams will cause unwanted things such as skin irritation, black spots appearing, poisoning to cause skin cancer. This study aims to determine the content and amount of mercury (Hg) and hydroquinone levels in whitening creams seen in traditional markets in Palu City. The sample of facial whitening cream under study was taken based on the purposive sampling method with the criteria of the sample that did not have a registration number, did not have an MUI halal certificate, did not contain active ingredients and did not have a BPOM number. Testing of hydroquinone levels was carried out using the Gas Chromatography-Mass Spectrometry (KGSM) method and testing for mercury (Hg) levels using the Atomic Absorption Spectrophotometer (AAS) method along with the additional MVU (Mercury Vaporizer Unit) method. Based on the measurement results, it was found that the highest levels of mercury (Hg) were sample B = 44.06 Î¼g / g and the lowest was sample G = 13.89 Î¼g / g and the results of hydroquinone levels were all negative. Of all the samples that have been studied all contain mercury (Hg) and negative contain hydroquinone.